How to write a good research grant proposal. Issue 3 (March 2016) - Barker, Lisa; Rattihalli, Rohini R.; Field, David
Abstract: This article aims to provide a step-by-step overview of the process of applying for research funding and will be most relevant to either a new academic joining a group or a young clinician wanting to establish their own research. The article covers the steps involved in preparing, writing and submitting an application. Included is a description of the different types of funding available, how to choose the right funding body, a discussion of the various people who should be involved in developing the research proposal (including the role of patient and public engagement in research) and the sources of support available to help the new researcher take their ideas forward. A checklist is provided to reiterate the key points.